The Cohort of Indonesian Preterm Infants for Long-term Outcomes (CIPTO) study: a protocol - Rinawati Rohsiswatmo; Hardya Gustada Hikmahrachim; Muhamad Azharry Rully Sjahrulla; Putri Maharani Tristanita Marsubrin; Risma Kerina Kaban; Rosalina Dewi Roeslani; Adhi Teguh Perma Iskandar; Distyayu Sukarja; Ahmad Kautsar; Ivo Urwah; Hartono Gunardi; Yoga Devaera (BMC, 2023)
Abstract Background Indonesia has high numbers of preterm birth, i.e., around 600,000 preterm births annually. It imposes a significant burden on the Indonesia's healthcare system. Indonesia therefore requires its own evidence-based reference to manage premature neonates and ex-preterm infants who subsequently survived. No long-term study on preterm infants in Indonesia has been conducted, therefore we aim to evaluate growth and development on ex-preterm infants until the pre-pubertal stage. Methods We at the Cipto Mangunkusumo General Hospital (CMGH) designed a prospective cohort study of preterm infants, i.e., the Cohort of Indonesian Preterm Infants for Long-term Outcomes (CIPTO) study. At least 500 subjects will be recruited with an estimation of two-year recruitment (i.e., the recruitment phase will be completed before 2024). The CIPTO study will observe long-term outcomes of ex-preterm infants, primarily on growth and developmental milestones until 8 years old. Aims of this study are to determine the ex-preterm outcomes and to generate an evidence-based reference of preterm care for ensuring optimum outcomes. The pre-specified long-term outcomes in this study are survival rates, growth outcomes, neurodevelopmental outcomes, feeding behavior, as well as hearing and vision impairments. Growth and neurodevelopmental outcomes will be assessed at 0, 2, 4, 6, 9, 12, 15, 18 and 24 months of corrected age as well as at 3, 4, 5, 6, 7 and 8 years old. Discussion The CIPTO study is the first prospective cohort in Indonesia focusing on preterm infants born at the CMGH. With a follow up until 8 years old, this study may provide useful insights to generate an evidence-based, Indonesia's health care reference in managing premature infants and ensuring the optimum outcomes of ex-preterm infants.